Rhabdomyolysis in Children Under Treatment for Diabetic Ketoacidosis at National Institute of Child Health - Syeda Sadia Ahmed, Mashal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the frequency of rhabdomyolysis in children under treatment for Diabetic Ketoacidosis (DKA) at National Institute of Child Health (NICH). Materials and Methods: Total 100 patients who were suffering from DKA were enrolled. Blood and urine samples were collected from of each child in aseptic conditions in sterilized container and sent for base line labs, urine ketone and serum creatinine kinase (CK) levels. All the demographic details and duration of diabetes mellitus and DKA and its treatment were recorded on a predesigned data collection proforma. Results: Out of 100 patients, 43 were male and 57 were female with mean age of 9.79±3.26 years. Seventy percent of the patients were aged 7.1-14 years, followed by 25.0% patients were aged 1-7 years and only 5.0% patients were aged of 14.1-18 years. The Mean duration of DM and DKA were 3.89±2.75 years and 9.72±4.65 hours respectively. Mean RBS, Urea and Creatinine level were 404.9± 99.1, 35.70±27.5 mg/dl and 0.73±0.75 mg/dl respectively. Mean hemoglobin and WBC level were 13.61±14.3 g/l and 16.33±11.8 respectively. The mean Na level was 137.79±5.64 mmol/l, mean K level was 4.01±0.89 mmol/l, mean Phosphorus level was 27.6±42.0 mg/dl and mean Cl level was 106.8±6.3 mmol/l. The mean PH was found 7.1±6.49 and mean Bicarbonate was 7.56±3.01 mmol/l. Fifty two percent patients were treated for more than 24 hours and 48.0% patients were treated for less than 24 hours. 7% patients under treatment for DKA were suffered from Rhabdomyolysis and expiry was 5%. Practical implication: In this study we find out that there is very little chance of causing rhabdomyolysis under treatment for DKA but we should take precautionary measures to prevent its progression towards its complications i.e., renal failure and cardiac Arrest which can lead to mortality. This study will lead a positive role in early cure of the DKA patients to avoid further complication. Conclusion: It is concluded that in DKA patients Rhabdomyolysis is of clinical concern because it can result in significant morbidity and mortality by causing Acute Renal failure, DIC, Cardiac Arrest, Arrythmias, significant electrolyte imbalance, but there is very little chance of causing rhabdomyolysis under treatment for DKA in our setup and it too can be avoided by early and aggressive treatment of DKA. Keywords: Rhabdomyolysis, Diabetic Ketoacidosis, Children, Hemoglobin , Creatinine